INFLUENCES OF LEADERSHIP AND MOTIVATION ON THE SPIRIT OF EMPLOYEES DINAS TENAGA KERJA, TRANSMIGRASI DAN KEPENDUDUKAN PROVINSI RIAU - Eric Rholando Silalahi; Dewita Suryati Ningsih; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study was conducted at the Dinas Tenaga Kerja, Transmigrasi Dan Kependudukan Provinsi Riau in order to determine how the influences of Leadership And Motivation simultaneous and partially to Employee Morale Dinas Tenaga Kerja, Transmigrasi Dan Kependudukan Provinsi Riau. And also to find out how Leadership Influence indirectly through Morale Motivation on the Dinas Tenaga Kerja, Transmigrasi Dan Kependudukan Provinsi Riau. The population in this study were employees Dinas Tenaga Kerja, Transmigrasi Dan Kependudukan Provinsi Riau, amounting to 261 people, with a total sample of 72 respondents. The sampling method used is proportionate startifield random sampling, sampling of members of the population at random and stratified proportional. Tests of data quality using Validity and reliability test, the classical assumption test, the MSI method, and the method of path analysis using SPSS version 21. The results of the testing that has been done, stating that the former leadership and motivation simultaneously and contribute significantly to the morale. The second leadership and motivation partial influences on morale. And the third indirect influences of leadership on morale through motivation So from this study in the spirit of the variables that must be improved is to give a sense of satisfaction to the employees, the leadership variables that must be improved is the leader must be more active in assessing the work of their employees, and the motivation variable that should be improved is to give encouragement or spirit to its employees in job.Keywords: Leadership, Motivation, and Morale.